Energy Efficiency Development in Indonesia: An Empirical Analysis of Energy Intensity Inequality - Setyawan, Dhani; Wardhana, Irwanda Wisnu (International Journal of Energy Economics and Policy, 2020)
Indonesia comprises a vast geographic region where a noticeable imbalanced of resource allocations have been impacting a significant disparity amongst regions. Some research has been conducted to measure income inequality in Indonesia, however, there was no study has been done to measure energy usage disparities in Indonesian case, specifically in the provincial level. This study proposes to investigate the disparities of energy usage levels specifically in energy intensity amongst 33 provinces in Indonesia from 2010-2015 by employing several indicators including Kernel Density Estimator, Gini Coefficient, Theil Index, Atkinson Index, and the Coefficient of Variation. The results capture the existence of a convergence process in energy usage across the 33 provinces in Indonesia during 2010 and 2015. Overall, this study concludes that energy efficiency process in Indonesia has been improved over the study period. Keywords: Energy Efficiency, Disparities, Energy Intensity, Indonesia JEL Classifications: Q43, O13, O11 DOI: https://doi.org/10.32479/ijeep.8808